Determination of chemisorption probabilities of hydrogen molecules on a nickel surface by artificial neural network - Boyukata, Mustafa (Array, 2008)
Summary: Dissociative chemisorption probabilities for H2(v, j) + Ni(100) collision systems have been estimated by using Artificial Neural Network (ANN). For training, previously determined probability values via molecular dynamics simulations have been used. Performance of the ANN, for predicting any quantities in the molecule-surface interaction, has been investigated. Effects of the surface sites and the rovibrational states of the molecule on the process are analyzed. The results are in good agreement with the related previous studies